LoGHeD: an effective approach for negative differential resistance effect suppression in negative-capacitance transistors. (14th January 2022) - Xie, Ziqiang; Lü, Weifeng; Guo, Mengxue; Zhao, Mengjie
Abstract: A negative capacitance transistor with fully depleted silicon-on-insulator (FDSOI) technology (NC-FDSOI) is one of the promising candidates for next-generation low-power devices. However, it suffers from the inherent negative differential resistance (NDR) effect, which is very detrimental to device and circuit designs. Aiming at overcoming this shortcoming, this paper proposes for the first time to use local Gaussian heavy doping technology (LoGHeD) in the channel near the drain side to suppress the NDR effect in the NC-FDSOI. The technical computer-aided design simulation results have validated that the output conductance ( G DS ) with LoGHeD, which is used to measure the NDR effect, increases compared to the conventional NC-FDSOI counterpart and approaches zero. With the increase in doping concentration, the inhibitory capability of the NDR effect shows a monotonously increasing trend. In addition, the proposed approach maintains and even enhances performances of the NC-FDSOI transistor regarding the electrical parameters, such as threshold voltage ( V TH ), sub-threshold swing, switching current ratio ( I ON / I OFF ), and drain-induced barrier lowering.